Publisher's Note: Measurement of the ratio of branching fractions B(B[bar]0→D*+τ-ν[bar]τ)/B(B[bar]0→D*+μ-ν[bar]μ) - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Physical review letters, 2015)
DOI:https://doi.org/10.1103/PhysRevLett.115.159901